Blood flow restriction training: a new approach for preventing and treating sarcopenia in older adults - Li, Wei; Hu, Mingzhen; Yin, Qiushi; Liu, Yuqing; Chen, Lin; Ru, Qin; Xu, Guodong; Wu, Yuxiang (Frontiers in Physiology, 2025)
With the intensification of population aging, sarcopenia in older adults has become a significant public health issue affecting quality of life. Sarcopenia is a progressive and systemic skeletal muscle disorder characterized by reduced muscle mass, decreased muscle strength, and diminished physical function. Although conventional exercise interventions have shown some efficacy in managing sarcopenia, their effects are limited and often insufficient to effectively halt disease progression. Therefore, exploring more efficient exercise interventions is of great importance. Blood flow restriction training (BFRT), as an emerging exercise intervention, has garnered increasing attention in recent years for its application in sarcopenia among older adults. Studies suggest that, compared to traditional resistance exercise, BFRT demonstrates superior effectiveness in improving muscle strength and mass in older adults, potentially serving as a viable alternative to conventional training methods. However, BFRT also presents certain limitations, including potential risks such as cardiovascular responses and muscle injury. Therefore, careful consideration of appropriate application scenarios and exercise loads is crucial during its implementation. This study reviews the biological mechanisms of BFRT in the intervention of sarcopenia and proposes tailored training protocols and application models for older adults. Furthermore, it thoroughly examines the potential risks and applicability of BFRT, aiming to provide theoretical foundations and practical guidance for clinical application. Additionally, the limitations of current research are analyzed, offering recommendations for future research directions.